2006
DOI: 10.1007/s10267-005-0270-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and physiological ecology of ammonia fungi: studies using natural substrates and artificial media

Abstract: Experiments using natural substrates and artificial media were categorized into three groups. Using experiments in these three categories, we investigated dispersion, invasion sequence, and decomposing ability of ammonia fungi in the field on natural substrates. Spore germination and vegetative and reproductive growth of ammonia fungi derived from monocultures and five-species cultures were assessed on natural substrates and on artificial media. These features assist understanding of the colonization and succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 39 publications
(45 reference statements)
1
45
0
Order By: Relevance
“…According to the sequential occurrence of ammonia fungi in the fi eld, they are divided into two types, early-phase fungi (EP fungi) and late-phase fungi (LP fungi). The former type species are saprobic fungi and living propagules of several EP fungi in the fi eld (Suzuki et al 2002;Suzuki 2006) and the spore longevity of the LP fungus H. spoliatum (Suzuki 2003). However, we do not yet have enough data to elucidate the propagation mechanism of each ammonia fungus.…”
Section: Introductionmentioning
confidence: 99%
“…According to the sequential occurrence of ammonia fungi in the fi eld, they are divided into two types, early-phase fungi (EP fungi) and late-phase fungi (LP fungi). The former type species are saprobic fungi and living propagules of several EP fungi in the fi eld (Suzuki et al 2002;Suzuki 2006) and the spore longevity of the LP fungus H. spoliatum (Suzuki 2003). However, we do not yet have enough data to elucidate the propagation mechanism of each ammonia fungus.…”
Section: Introductionmentioning
confidence: 99%
“…Yamanaka (1999Yamanaka ( , 2003 pointed out that the successive appearance of ammonia fungi from EP to LP species may be controlled by the changes in both pH and the form of inorganic nitrogen. Suzuki (1989Suzuki ( , 2006 also proposed that the sequential propagation of each ammonia fungi may be explained by their preference of or tolerance to high concentrations of ammonium nitrogen under alkaline to neutral conditions as well as by their adaptation to different pH conditions.…”
Section: Discussionmentioning
confidence: 97%
“…In the former, physiological characteristics of spore germination (Suzuki 1978(Suzuki , 1989(Suzuki , 2006Suzuki et al 1982), vegetative growth, and reproductive structure formation (Morimoto et al 1981(Morimoto et al , 1982Enokibara et al 1993;Soponsathien 1998a,b;Yamanaka 1999Yamanaka , 2001Yamanaka , 2003He and Suzuki 2003;Suzuki 2006;Licyayo and Suzuki 2006) have been examined. In the latter, only Suzuki (2006) made preliminary studies of interspecifi c interactions among a few ammonia fungi and reported that the early-stage EP fungi Amblyosporium botrytis and Ascobolus denudatus showed mutual intermingling under acidic to alkaline conditions and that the LP fungus Hebeloma vinosophyllum increased fruiting and invaded into the colony of Amblyosporium botrytis under acidic conditions. The objective of this article is to examine and characterize the in vitro interactions among members of ammonia fungi and to provide insight into how these interactions infl uence their vegetative and reproductive growths in the natural habitat resulting in their successive occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Authors of these studies fi rst considered fruit-body assemblages (Bills et al 1986; ammonia fungi are rarely seen under natural conditions, they are not necessarily dependent on artifi cial disturbance for their growth and reproduction. They are considered to be latent inocula in soils (Sagara 1976b;Suzuki et al 2002;Suzuki 2006) of forests in various areas and to be adapted to many kinds of local but frequent input disturbances, e.g., animal excretions, carcasses, or giant-hornet wastes (Sagara et al 1985;Sagara 1989Sagara , 1995Wang and Sagara 1997;Fukiharu et al 2000a,b;Harmaja 2002;Kasuya 2002;Oda et al 2002).…”
Section: Introductionmentioning
confidence: 98%